DESIGNATION OF ORIGIN AND GEOGRAPHICAL INDICATIONS - Ioan Tomescu (Perspectives of Law and Public Administration, 2022)
The production, manufacturing and distribution of agricultural and food products play an important role in the state economy, but also in that of the European Union. The diversification of agricultural production can lead to a better balance between supply and demand. Moreover, it brings an economic benefit to the rural area by promoting products with specific characteristics in disadvantaged or remote areas, ensuring the increase in the population's income in these areas. At European level, a protection system has been established to ensure protection in each Member State of the European Union, which encourages the increasing use of the terms 'geographical indications' and 'designations of origin', an approach which deals with the optimal registration conditions for an equal competition between the producers, increased guarantees for the consumers that these designations clearly constitute a quality guarantee, as they allow the preservation of the specificity of the product. Similar to other Member States of the Union, in 2011 Romania transmitted to the European Commission, according to the provisions of Regulation (EC) no. 1234/2007, the technical specifications corresponding to all the controlled designations of origin (DOC) and geographical indications (GI) for products used at national level, drawn up by the producers’ associations established in the geographical areas demarcated by DOC and GI, in order to ensure their protection based on the above-mentioned European legislation.